Noragami, stray god. 18 - Adachi, Toka (Kodansha Comics, 2017)
"Now that Yato has defeated Takemikazuchi, he must protect Bishamon long enough for the thunder god to convince the Heavens to call off their punishment. Meanwhile, Yukin. strives to keep Yato and the crafter alive to ensure Yato's safety, but when Bishamon takes deadly aim at Kōto, Yukin. resorts to drastic measures."--Back cover.